The Genetic Structuralism Analysis of Dyslexic in Rick Riordan’s Percy Jackson and The Olympians: The Lightning Thief - Muqoyyid Dinillah Al-Jawwad (Fakultas Ilmu Budaya, 2025)
Percy Jackson and The Olympians: The Lightning Thief by Rick Riordan is a novel that tells the story of a 12-year-old boy named Percy Jackson who has dyslexia and dreams of understanding his place in the world. Unfortunately, his learning difference creates significant challenges in his educational and social life, forcing Percy to struggle with feelings of inadequacy and confusion about his identity. Percy is a student living in New York with his single mother and works hard to succeed in school despite his learning challenges. Here, Percy represents a young person with learning differences who fights against misconceptions and discrimination in his environment. At this time, educational systems often fail to recognize and support students with learning differences. Young people with dyslexia are frequently marginalized in traditional academic settings. They are excluded from opportunities and face not just one form of discrimination but multiple layers of misunderstanding. These struggles make young people with dyslexia want the same opportunities and recognition as their neurotypical peers to live and learn as they wish. There are two discussions in this research. The first is about how Percy Jackson, in the early 21st century, struggled against the challenges of having dyslexia in getting education and social acceptance. Then, it is connected with the social context of American society where the novel was published. The second is how Riordan, as the novel's author, views the issues of learning differences and social acceptance experienced by individuals with dyslexia in this novel. This study uses genetic structuralism theory from Lucien Goldmann with a dialectical approach. This theory is used because the object of this analysis uses text from novels, and there is a relationship with specific social and educational contexts. This discussion uses a qualitative research type because the text is the primary data in this analysis. The result of this thesis shows that in the novel, dyslexia initially make it difficult for Percy to gain acceptance and success because of the marginalization he experiences in traditional educational settings. To change his understanding of himself and realize his potential, Percy discovers that his dyslexia is actually connected to his demigod heritage and represents a different way of processing information. However, this revelation requires him to leave his familiar world and accept a new identity, which brings both opportunities and challenges. The reframing of dyslexia as a strength rather than a disability provides hope for individuals with learning differences, since it suggests that what society often sees as limitations may actually be different forms of ability. Nowadays, the challenges faced
Reupload file repository 29 Januari 2026_Ratna
Keywords: Percy Jackson and The Olympians: The Lightning Thief